Tidal inlet migration and formation: the case of the Ararapira inlet – Brazil (Ocean and Coastal Research, 2020)
The aim of this study is to assess the morphological evolution of the Ararapira (Brazil) barrier-inlet system, at different time scales. Based on satellite imagery, elevation data, and in-situ observations, we quantify the morphological evolution of the region. Results show that the Ararapira inlet migrated continuously southwards, moving updrift, with erosion at its southern margin and intercalated erosion and accretion at the northern margin. At approximately 5.5 km north of the old inlet, the gradual narrowing of the sandy barrier due to channel meandering and coastal erosion resulted in its breaching, in August 2018. We document the initial stages of the new inlet, which after opening, presents intense erosion at its southern margin, resulting in the channel widening to ~1 km. After the barrier breaches, the system begins to adjust to a new equilibrium condition, with the widening of the new inlet being balanced by the gradual closure of the old inlet. These drastic environmental changes control the functioning of such systems, and our results provide important background information for their use and management.